The KIT D816V allele burden predicts survival in patients with mastocytosis and correlates with the WHO type of the disease. Issue 6 (17th April 2014) - Hoermann, G.; Gleixner, K. V.; Dinu, G. E.; Kundi, M.; Greiner, G.; Wimazal, F.; Hadzijusufovic, E.; Mitterbauer, G.; Mannhalter, C.; Valent, P.; Sperr, W. R.
Abstract KIT D816V is present in a majority of patients with systemic mastocytosis (SM). We determined the KIT D816V allele burden by quantitative real‐time PCR in bone marrow and peripheral blood of 105 patients with mastocytosis. KIT D816V was detected in 92/105 patients (88%). Significant differences in the median allele burden were observed between disease subgroups: cutaneous mastocytosis (0.042%), indolent SM (0.285%), smoldering SM (5.991%), aggressive SM (9.346%), and SM with associated hematologic non‐mast cell lineage disease (3.761%) (P < 0.001). The KIT D816V burden also correlated with serum tryptase (R = 0.5, P < 0.005) but not with mast cell infiltration in bone marrow or mediator symptoms. Moreover, the allele burden was of prognostic significance regarding survival (P < 0.01). Patients responding to cytoreductive therapy showed a significant decrease in KIT D816V (P < 0.05). To conclude, the KIT D816V burden correlates with the variant of mastocytosis, predicts survival, and is a valuable follow‐up parameter in SM.